Less State, More Market: University Reform in Canada and Abroad - Schuetze, Hans G.; Bruneau, William (Canadian Journal of Higher Education, 2004)
Political, economic, and social explanations of higher education reform, and the very definition of "reform," are the main departure points of this volume. The introduction uses the examples of Canada, Austria, Germany, and Japan to show that in all these countries, reform has meant reduced state funding and control and increased reliance on market mechanisms, private sources of funding, and new forms of university governance and management.